1991
DOI: 10.1073/pnas.88.6.2222
|View full text |Cite
|
Sign up to set email alerts
|

Dual site model for the organogenic activity of angiogenin.

Abstract: The residues that are indispensable for the ribonucleolytic activity of angiogenin are also known to be essential for its angiogenic activity. We now demonstrate that residues in another region of the protein, devoid of catalytic residues, are additionally required for angiogenesis. Endoproteinase Lys-C or a baby hamster kidney cell protease cleaves angiogenin at the peptide bond either between Lys-60 and Asn-61 or between Glu-67 and Asn-68, respectively. The two polypeptide fragments resulting from either cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 30 publications
8
106
0
Order By: Relevance
“…The extremely tight-binding inhibitor of pancreatic RNase (Blackburn et al, 1977;Lee et al, 1989), binds avidly to RNase 4 (Shapiro et al, 1986a), as it does to angiogenin (Lee et a]., 1989) and RNase 2 (Shapiro and Vallee, 1991). This signals a coinciding need for close control of the activities of these enzymes and implies a specific biological function for the relatively rarc RNase 4, and perhaps even Tor RNase 1, which has yet to be found.…”
Section: Functional Implications Of the Rnase-4 Sequencementioning
confidence: 99%
See 2 more Smart Citations
“…The extremely tight-binding inhibitor of pancreatic RNase (Blackburn et al, 1977;Lee et al, 1989), binds avidly to RNase 4 (Shapiro et al, 1986a), as it does to angiogenin (Lee et a]., 1989) and RNase 2 (Shapiro and Vallee, 1991). This signals a coinciding need for close control of the activities of these enzymes and implies a specific biological function for the relatively rarc RNase 4, and perhaps even Tor RNase 1, which has yet to be found.…”
Section: Functional Implications Of the Rnase-4 Sequencementioning
confidence: 99%
“…As in the case of angiogenin (Hallahan et al, 1991), these changes might involve non-active-site regions that are related to other, as yet unknown: aspects of RNase-4 function. The deletion at postitions 77 and 78 is superficially easy to accommodate in the RNase structure, as these residues protrude from the 8-sheet structure and do not participate in the hydrogen bonding characteristic for 8 sheets (Wlodawer et al, 1982).…”
Section: Functional Implications Of the Rnase-4 Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…19 Of special interest are the studies performed by site -specific mutagenesis to identify those residues significant for ribonuclease and angiogenic activity of the molecule. In most instances, the efficacy of angiogenin in performing both activities is correlated, although Hallahan et al 27 have suggested that the RNase active site in angiogenin is essential, but not sufficient, for its angiogenic activity, and that an additional second site on the molecule is required.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for an optimal recovery of these proteins at the purification stage. The following is a sample of papers that used this protocol to recover biotinylated proteins: [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Following the pre-adsorption phase, the column was then washed with 16 ml of 10 % acetic acid and 0.1 M NaHPO 4 until the pH of the flow-through was >6.8.…”
Section: Biotin Avidin Columnmentioning
confidence: 99%